Deskriptif Caregiver Dalam Merawat Pasien Gangguan Jiwa - Arini, Larasuci; Ardi, Zadrian; Syarli, Setiadi; Daharnis, Daharnis (Pustaka Galeri Mandiri, 2025)
This study aims to describe the psychosocial conditions of caregivers who care for patients with mental disorders and identify their needs for guidance and counseling services. Using a quantitative approach with a descriptive design, 45 caregivers in the working area of the Pariaman City Community Health Center were selected as research respondents through random sampling. Data were collected using a structured questionnaire measuring care burden, coping strategies, social support, and other psychosocial needs. The results of the study indicate that the majority of caregivers experience moderate to heavy care burdens, with dominant coping strategies being passive and religious in nature. The social support received primarily comes from the immediate family, while community support remains low due to stigma surrounding mental disorders. A total of 88.9% of caregivers reported needing counseling and guidance services. These findings underscore the importance of psychosocial assessment as a foundation for developing contextually appropriate counseling interventions to enhance caregivers' mental resilience and support patients' holistic recovery..